Analysis of the Results of Bustier Production Using Inserted Boning, Sewn Boning, and Steel Boning - Muhammad Wahyu Gunawan; Romadhona Chusna Tsani (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2026)
A bustier plays a crucial role in supporting the body, enhancing its shape, and enhancing aesthetics, especially when worn with a kebaya or evening gown. This study aims to analyze the results of bustier production using three different types of boning, such as needle-inserted boning, sewn-in boning, and steel boning, to determine the most optimal type of boning. The method used is Research and Development (R&D), encompassing data collection, product design, validation, testing, and product revision. This study found that the bustier with inserted boning achieved fairly good results with an average score of 3.00, which equates to 75.00% and falls into the “acceptable” category, while the bustier with sewn-in boning demonstrated the most optimal results. Based on validation testing by two expert validators, this product received an average score of 3.64 out of a total of 4, with a 90.91% acceptability rate, which falls into the “highly acceptable” category. The bustier with steel boning received an average score of 2.82, or 70.45%, which also falls into the “acceptable” category. Steel boning is not yet widely available, so its availability should be confirmed before production begins. Installing both sewn boning and steel boning requires precision. Therefore, it is recommended that you first practice structural sewing techniques.